Historical Reconstruction of Multiethnic Society in The Process of Establishing a New Autonomous Region Part of East Sulawesi - Mursalat Kulap (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This paper describes how the role of historical reconstruction in the process of formationof the Autonomous Region of New prospective East Sulawesi Province. In the process offormation of new autonomous regions, the needed awareness as a community identity,especially in the multiethnic society. Through history rekostruksi holistically, thenindirectly have formed an acknowledgment of the existence of groups - ethnic groups inthe eastern region of Sulawesi, and is expected to be a cornerstone of the power struggleof the formation of East Sulawesi province that is still ongoing. Not only as a foundationof identity, historical reconstruction will also be the foundation for the continuity ofdevelopment after the province was formed.Keyword : Historical Reconstruction, Multiethnic Society, New AutonomousRegion, East Sulawesi.